Thyroid cancer complicating familial adenomatous polyposis: mutation spectrum of at-risk individuals - Septer, Seth (BioMed Central, 2013)
BACKGROUND: Lifetime risk of thyroid cancer associated with FAP has been reported as 1-2%. The mean age at diagnosis of thyroid carcinoma in FAP has been reported at 28 years. The aims of this paper are to better understand gene mutations associated with thyroid cancer and refine surveillance recommendations for patients with FAP. METHODS: We performed a search in Pubmed, Ovid Medline and Embase with the terms ("Thyroid Gland"[Mesh] OR "Thyroid Neoplasms"[Mesh]) AND "Adenomatous Polyposis Coli"[Meshdenomatous Polyposis Coli"[Mesh] to identify subjects with thyroid cancer and FAP. As a reference group for APC mutations in the unselected FAP population, we used the UMD-APC database referenced in the Orphanet portal, which includes APC mutation data on 2040 individuals with FAP. RESULTS: There were 115 reported cases of thyroid cancer in patients with FAP (95 female: 11 male) with an average age of 29.2 years. Gene mutation testing results were reported in 48 patients. On comparing the prevalence of APC mutation in the population of FAP patients with thyroid cancer and the prevalence of the same mutation in the reference population an increased odds ratio was evident in individuals harboring an APC mutation at codon 1061 (OR: CI 4.1: 1.7-8.9). Analysis of the prevalence of thyroid cancer in individuals with FAP segregated by the region of the gene affected shows an increased risk of thyroid cancer in individuals harboring mutations proximal to codon 512 (OR 2.6, p 0.0099). CONCLUSIONS: There is increased risk for thyroid cancer in individuals with APC mutations at the 5' end (proximal to codon 528) along with the established high risk group harboring mutation at codon 1061. It is suggested that these patients might benefit from directed surveillance by annual ultrasound from age 18 years onwards.